PENGETAHUAN, PENDAPATAN, DAN KEMAJUAN TEKONOLOGI TERHADAP MINAT INVESTASI MASYARAKAT DI PASAR MODAL (STUDI KASUS MASYARAKAT KABUPATEN BLITAR) - Fiqrianur Haikal; Deny Yudiantoro; Amalia Nuril Hidayati (Bajang Institute, 2022)
The data findings in this study are useful for finding and seeing the impact of technological knowledge, technological income, and technological progress on the investment interest of the people of Blitar Regency in the capital market in Blitar Regency. The approach in this study using a quantitative approach. Data collection techniques in this study used a questionnaire questionnaire. Sources of data in this study with primary data amounting to 90 respondents from the people of Blitar Regency. The data that has been collected is then tested using SPPS, namely testing several tests which include, reliability test, data normality test, multicollinearity test, heteroscedasticity test, T test, and F test. on the investment interest of the people of Blitar Regency in the capital market. Partially, the technology income variable (X2) has no influence on the investment interest of the people of Blitar Regency in the capital market. Partially, the technological progress variable (X3) has an influence on the investment interest of the people of Blitar Regency in the capital market.